2011
DOI: 10.1103/physrevb.84.024102
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectric properties of polydomain epitaxial Pb(Zr1x,Tix)

Abstract: The pyroelectric properties of polydomain epitaxial Pb(Zr 1-x ,Ti x )O 3 thin films are investigated using a Ginzburg-Landau-Devonshire thermodynamic model. We explore the three major contributions to pyroelectric response in thin films including intrinsic effects and previously neglected contributions such as extrinsic and secondary effects, to provide a complete picture of pyroelectric property development. The pyroelectric coefficient for epitaxial thin films is calculated as a function of strain, temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 40 publications
5
56
0
Order By: Relevance
“…This is due to clamping enhanced pyroelectric coefficient, the mechanism of which has been already discussed in detail. [55][56][57] Additionally, room temperature dielectric constant (ε) and loss (tan δ) as a function of frequency have been measured. Figures 6(a) and 6(b), represent dielectric constant (ε) and loss (tan δ) respectively for pure and glass added BNT-BT-ST ceramics.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to clamping enhanced pyroelectric coefficient, the mechanism of which has been already discussed in detail. [55][56][57] Additionally, room temperature dielectric constant (ε) and loss (tan δ) as a function of frequency have been measured. Figures 6(a) and 6(b), represent dielectric constant (ε) and loss (tan δ) respectively for pure and glass added BNT-BT-ST ceramics.…”
Section: Resultsmentioning
confidence: 99%
“…We note that our previous studies on perovskite ferroelectrics 20,21 showed no significant differences in the structural or the functional properties between films grown on the same substrates by the two different methods, making the choice of substrate the defining parameter in our study. We could therefore compare domain wall transport in samples with very different oxygen vacancy densities and substrate chemical properties 22 but similar high crystalline 23,24 and surface quality.…”
Section: )O 3 Thin Filmsmentioning
confidence: 99%
“…The first term represents the intrinsic electrocaloric response due to a temperature dependent change in the magnitude of the polarization within the domains. Since the equilibrium c domain population / 0 depends on temperature, we also have an extrinsic contribution 19 to the primary electrocaloric coefficient as shown in the second term. The polydomain thermodynamic theory enables us to calculate the intrinsic and extrinsic contributions as a function of the applied electric field.…”
Section: à ámentioning
confidence: 99%